Flexible Sample Environments for the Investigation of Soft Matter at the European Spallation Source: Part I—The In Situ SANS/DLS Setup - Andreas Josef Schmid; Lars Wiehemeier; Sebastian Jaksch; Harald Schneider; Arno Hiess; Torsten Bögershausen; Tobias Widmann; Julija Reitenbach; Lucas P. Kreuzer; Matthias Kühnhammer; Oliver Löhmann; Georg Brandl; et al. (Applied Sciences, 2021)
As part of the development of the new European Spallation Source (ESS) in Lund (Sweden), which will provide the most brilliant neutron beams worldwide, it is necessary to provide different sample environments with which the potential of the new source can be exploited as soon as possible from the start of operation. The overarching goal of the project is to reduce the downtimes of the instruments related to changing the sample environment by developing plug and play sample environments for different soft matter samples using the same general carrier platform and also providing full software integration and control by just using unified connectors. In the present article, as a part of this endeavor, the sample environment for in situ SANS and dynamic light scattering measurements is introduced.